Dr Google in the ED: searching for online health information by adult emergency department patients. Issue 8 (20th August 2018) - Cocco, Anthony M; Zordan, Rachel; Taylor, David McD; Weiland, Tracey J; Dilley, Stuart J; Kant, Joyce; Dombagolla, Mahesha; Hendarto, Andreas; Lai, Fiona; Hutton, Jennie
Abstract: Objective: To determine the prevalence, predictors, and characteristics of health‐related internet searches by adult emergency department (ED) patients; to examine the effect of searching on the doctor–patient relationship and treatment compliance. Design: A multi‐centre, observational, cross‐sectional study; a purpose‐designed 51‐item survey, including tools for assessing e‐health literacy (eHEALS) and the effects of internet searching on the doctor–patient relationship (ISMII). Setting, participants: 400 adult patients presenting to two large tertiary referral centre emergency departments in Melbourne, February–May 2017. Outcome measures: Descriptive statistics for searching prevalence and characteristics, doctor–patient interaction, and treatment compliance; predictors of searching; effect of searching on doctor–patient interaction. Results: 400 of 1056 patients screened for eligibility were enrolled; their mean age was 47.1 years (SD, 21.1 years); 51.8% were men. 196 (49.0%) regularly searched the internet for health information; 139 (34.8%) had searched regarding their current problem before presenting to the ED. The mean ISMII score was 30.3 (95% CI, 29.6–31.0); searching improved the doctor–patient interaction for 150 respondents (77.3%). Younger age (per 10‐year higher age band: odds ratio [OR], 0.74; 95% CI, 0.61–0.91) and greater e‐health literacy (per one‐point eHEALS increase: OR, 1.11; 95% CI, 1.06–1.17) predicted searching the current problem prior to presentation; e‐health literacy predicted ISMII score (estimate, 0.39; 95% CI, 0.20–0.39). Most patients would never or rarely doubt their diagnosis (79%) or change their treatment plan (91%) because of conflicting online information. Conclusion: Online health care information was frequently sought before presenting to an ED, especially by younger and e‐health literate patients. Searching had a positive impact on the doctor–patient interaction and was unlikely to reduce adherence to treatment.